Answer:
![(fof^{-1})(x)=x](https://tex.z-dn.net/?f=%28fof%5E%7B-1%7D%29%28x%29%3Dx)
Step-by-step explanation:
Composition of two functions f(x) and g(x) is represented by,
(fog)(x) = f[g(x)]
If a function is,
f(x) = (-6x - 8)² [where x ≤
]
Another function is the inverse of f(x),
![f^{-1}(x)=-\frac{\sqrt{x}+8}{6}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D-%5Cfrac%7B%5Csqrt%7Bx%7D%2B8%7D%7B6%7D)
Now composite function of these functions will be,
![(fof^{-1})(x)=f[f^{-1}(x)]](https://tex.z-dn.net/?f=%28fof%5E%7B-1%7D%29%28x%29%3Df%5Bf%5E%7B-1%7D%28x%29%5D)
= ![[-6(\frac{\sqrt{x}+8}{6})-8]^{2}](https://tex.z-dn.net/?f=%5B-6%28%5Cfrac%7B%5Csqrt%7Bx%7D%2B8%7D%7B6%7D%29-8%5D%5E%7B2%7D)
= ![[-\sqrt{x}+8-8]^2](https://tex.z-dn.net/?f=%5B-%5Csqrt%7Bx%7D%2B8-8%5D%5E2)
= ![(-\sqrt{x})^2](https://tex.z-dn.net/?f=%28-%5Csqrt%7Bx%7D%29%5E2)
= x
Therefore, ![(fof^{-1})(x)=x](https://tex.z-dn.net/?f=%28fof%5E%7B-1%7D%29%28x%29%3Dx)
Answer:
16/25
Step-by-step explanation:
first do keep change flip
4/5 × 4/5
16/25
Answer:
The last choice. The red one
Step-by-step explanation:
I'm just guessing at this point. But, by the looks of it, red does seem like it would be correct. Again, this is just a guess. So, if it's wrong I'm so sorry. Have a lovely day.
Answer is a, 57.49.
17.42-12.60-9.62= $-4.80+62.29=57.49